An investigation of negative affect, reactivity, and distress tolerance as predictors of disordered eating attitudes across adolescence. (June 2016) - Juarascio, Adrienne S.; Felton, Julia W.; Borges, Allison M.; Manasse, Stephanie M.; Murray, Helen B.; Lejuez, Carl W.
Abstract: The current study examined internalizing symptoms, affect reactivity, and distress intolerance as prospective predictors of increases in eating disorder (ED)-attitudes during adolescence. Adolescents (n = 206) took part in a six-year longitudinal study examining the development of psychopathology. Latent growth curve analysis was used to examine associations between predictors and later ED-attitudes. Distress intolerance and internalizing symptoms were associated with ED-attitudes at baseline, but did not predict increases over time. Affect reactivity, however, was significantly associated with increases in ED-attitudes over time. Baseline affect reactivity did not interact with baseline distress intolerance to predict increases in ED-attitudes; however higher baseline internalizing symptoms interacted with distress intolerance to predict increases in ED-attitudes across adolescence. These results are among the first to document that affect reactivity alone and the combined effect of high internalizing symptoms and high distress intolerance early in adolescence are risk factors for the later development of ED-attitudes.